{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# sol2 - ECE 5620 Spring 2011 Homework#2 Solutions 1 2 1 3 4...

This preview shows pages 1–6. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ECE 5620 Spring 2011 Homework #2: Solutions 1. 2. 1 3. 4. 2 5. 3 6. 7. (a) I ( X 1 ,X 2 ,...,X n ; Y ) = n X i =1 I ( X i ; Y | X 1 ,...,X i- 1 ) = n X i =1 [ H ( X i | X 1 ,...,X i- 1 )- H ( X i | X 1 ,...,X i- 1 ,Y )] ( i ) = n X i =1 [ H ( X i )- H ( X i | X 1 ,...,X i- 1 ,Y )] ( ii ) ≥ n X i =1 [ H ( X i )- H ( X i | Y )] = n X i =1 I ( X i ; Y ) , where ( i ) follows from the independence of the X 1 ,...,X n and ( ii ) follows because conditioning reduces entropy. (b) For equality in ( ii ) we require H ( X i | X 1 ,...,X i- 1 ,Y ) = H ( X i | Y ) for all i, which is equivalent to X i ↔ Y ↔ ( X 1 ,...,X i- 1 ) for all i. 8. Mimicking the “alternative” proof of the concavity of unconditional en- tropy, let ( X 1 ,Y 1 ) have joint PMF p 1 ( x,y ) and let ( X 2 ,Y 2 ) have joint PMF p 2 ( x,y ) . Suppose that T has PMF Pr( T = 1) = θ = 1- Pr( T = 2) . 4 Suppose that ( X 1 ,Y 1 ) , ( X 2 ,Y 2 ) , and T are all independent. Observe that ( X T ,Y T ) has joint PMF p ( x,y ) =...
View Full Document

{[ snackBarMessage ]}

### Page1 / 7

sol2 - ECE 5620 Spring 2011 Homework#2 Solutions 1 2 1 3 4...

This preview shows document pages 1 - 6. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online